Mediating online DNA-Dialogues - Radstake, Maud; Nelis, Annemiek; Heuvel-Vromans, Eefje van den; Dortmans, Koen (Technische Universität Dortmund, 2009)
In a pilot project called The DNA-Dialogues online discussion boards of popular magazines featured as sites for public dialogue on genomics-related issues. As organizers and mediators of those online discussions, we experienced problems that have hardly been attended to by dialogue practitioners nor by social scientists who study and criticize public engagement activities. We illustrate those problems with examples from an online discussion on the storage and use of neonatal screening blood. We draw two lessons. First, practitioners as well as analysts tend to consider dialogues as public engagement activities, whereas we learned that the engagement of experts is just as difficult and equally crucial. Second, the role played by organizers and moderators of dialogue events is often left implicit, whereas we actively contributed to framing the issue at stake in the discussion. As an alternative for the notion of dialogue as a form of public engagement, we propose to do dialogue as a form of interventionist social science research. We instigate an outline of what such interventionist dialogue research would involve, and argue that it requires an integration of the roles of dialogue practioner and critical analyst.
From public engagement to interventionist research
Science, Technology & Innovation Studies
Keywords: 300; 330